Notifications of acute diarrheal diseases in a municipality in the Pantanal (Research, Society and Development, 2021)
Acute Diarrheal Disease (ADD) is a global public health problem, with 1.7 billion childhood cases per year. Its occurrence may be related to social, cultural, nutritional and environmental factors, such as low coverage of basic sanitation and the dynamics of waters in a region. In situations of intense rain and flooding, cases of diarrhea tend to increase. Considering the above, the present study aims to compare the occurrence of diarrhea in Cáceres-MT in a time series (2015, 2017 and 2018 - 2016 was excluded due to lack of data) with the pluviometric and fluviometric indices. The occurrences of diarrhea were extracted from the SIVEP-DDA; the data on rainfall were obtained from tables available on the website of the National Institute of Meteorology and the data on the level of the river in spreadsheets fed and made available by the Brazilian Navy / West Nautical Signaling Service. In 2015, 2017 and 2018, 5,686 cases of diarrhea were recorded in Cáceres-MT. The results showed that the increase in occurrences of ADD is significantly related to the increase in the level of the Paraguay River. During the low water months, the occurrences of ADD reduce 28% in relation to the high water period, but without a significant relationship with the reduction in the level of the river. The use of untreated water at this time may be contributing to the increase in ADI, indicating a relationship between water dynamics and diarrhea cases in Cáceres-MT.